2005
DOI: 10.1681/asn.2004090783
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria and Lower Glomerular Filtration Rate at Young Adult Age in Subjects Born Very Premature and after Intrauterine Growth Retardation

Abstract: This prospective follow-up study of 422 19-yr-old subjects born very preterm in The Netherlands was performed to determine whether intrauterine growth retardation (IUGR) predisposes to abnormal GFR and microalbuminuria in adolescents. GFR (ml/min per 1.73 m 2 ) was estimated using the Cockcroft-Gault equation, and albumin-creatinine ratio (mg/mmol) was calculated in a cohort of 19-yr-old subjects born very preterm (gestational age <32 wk) in 1983. Birth weights were adjusted for gestational age and expressed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
159
4
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(178 citation statements)
references
References 28 publications
9
159
4
4
Order By: Relevance
“…7,[34][35][36] We found that IUGR was associated with low-normal kidney function in young adults from the general population. This is consistent with findings in subjects born very prematurely 17 . A low nephron number was observed in low-BW subjects at autopsy.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…7,[34][35][36] We found that IUGR was associated with low-normal kidney function in young adults from the general population. This is consistent with findings in subjects born very prematurely 17 . A low nephron number was observed in low-BW subjects at autopsy.…”
Section: Discussionsupporting
confidence: 93%
“…This could explain associations of low BW with such clinical outcomes as albuminuria, low-normal kidney function, and ESRD. [6][7][8][9][10][11][12][13][14][15][16][17]37 However, these are only a few studies, sometimes with a weak design, and the effects found were not strong. Case-control studies showed an OR of 1.5 for ESRD in subjects with BWs less than 2,500 g, but data for BW were missing in half the cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have tried to dissect the relative roles of prematurity and growth restriction. Some authors suggest prematurity alone is the predominant risk factor, whereas others have found SGA to be more important in determining risk of higher blood pressure and kidney disease 57 . These differences likely reflect the complex interplay of intra-and extra-uterine events and timing of insults which vary considerably in premature infants 12 .…”
Section: Birth Weight Prematurity and Blood Pressurementioning
confidence: 99%
“…Singh and Hoy (2004) described an association between low birth weight, kidney size, and albuminuria in Aboriginal Australians between 4 and 72 years of age. Recently, the Keijzer-Veen et al (2005) prospective follow-up study reported an association between the severity of IUGR and renal function in young adults who were born very prematurely. On average, their low birth weight was associated with lower glomerular filtration rates, higher serum creatinine concentrations, and higher microalbumin secretion at the age of 19.…”
Section: Discussionmentioning
confidence: 99%